Information graphics - Rendgen, Sandra; Wiedemann, Julius (Köln Taschen, 2018)
Seeing is understanding. How complex ideas can be communicated via graphics. Einstein once said: "If you can't explain it simply, you don't understand it well enough." The amount of data we deal with today is overwhelming for everyone, from newspaper readers to laboratory scientists. The good news is that there are professionals that dedicate their time and lives to helping people understand complex situations, data sets, or even simple schemes that can be communicated much easier via a drawing than with words. The book presents a historical perspective to the subject, highlighting the work of the masters of the profession who have created a number of breakthroughs that were eventually adopted as new visual ways to communicate. Advice from leading professionals such as Nigel Holmes, Paolo Ciuccarelli, Richard Saul Wurman, and Simon Rodgers is also included. Following an in-depth introduction are over 400 examples of works, each with a fact sheet and an explanation of methods and objectives
Texto en inglés, francés y alemán
Including a poster by Nigel Holmes
**Por su gran tamaño se coloca en SALA C**
Keywords: Diseño gráfico; Infografía; Comunicación visual; Gráficos de ordenador